Community Service to Improve Regional Product Development in Tuban, East Java Indonesia - W., Muslichah Erma; Retnowati, Nova; Slamet, Agus (Advances in Social Sciences Research Journal, 2019)
Batik has been designated by UNESCO as a Humanitarian Heritage for Oral and Non-Buddhist Culture (Masterpieces of the Oral and Intangible Heritage of Humanity). Tuban is one of the cities in Indonesia that produces superior Gedog batik products. Batik is a fabric drawn with a night that has certain peculiarities. The Regional Superior Product Development Program is a community service program with the aim of advancing the Tuban area through its batik products. The problem of partners in this production is the production process, marketing, operational activities, market penetration and also community resources. The results of this activity are (1) Counseling, practice, and assistance in increasing knowledge in the field of colouring and design. (2) Counselling, practice, and assistance in enhancing knowledge in the operational functions of HR management, Marketing, Finance and information and production. Knowledge and ability to manage a business with the knowledge of operational functions of basic knowledge management that is very necessary for managing businesses that must be owned by all organizational structures in the company. Orderliness in making financial and tax reports. Knowledge, ability and preventive measures to overcome problems from receiving raw materials to marketing.